2017
DOI: 10.5539/ach.v9n2p90
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Stigma Against the Bajo Tribe and its Impact on Local Culture: Study of the Bajo Tribe in Bungin Village of South Konawe

Abstract: This study aims to examine and analyze the negative stigma of Bajo tribe and its impact on the existence of the local culture of Bajo tribe. Data collection techniques are conducted through in-depth interviews, document studies and focused discussions. Data analysis is done through data reduction, data presentation and conclusion. The results show that the Bajo tribe is still regarded as an underdeveloped tribe, always viewed as a wild, unruly, rough, stubborn and introvert. Bajo tribe is also viewed as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
1
Order By: Relevance
“…Saladin S. Teo menyoroti pendidikan dan gaya hidup orang Bajo menyimpulkan bahwa secara umum perkembangan ilmu pengetahuan, kemajuan teknologi serta perubahan sosial tidak banyak mempengaruhi perubahan suku Bajo, termasuk aspek pendidikan dibandingkan dengan kelompok minoritas lainnya. Selain itu hasil penelitian menunjukkan bahwa suku bajo masih dianggap sebagai suku yang ketinggalan zaman, dipandang sebagai suku liar, susah diatrur, keras kepala, kasar, dan introvert (Basri et al, 2017). Kekuatan tradisi nenek moyang, penanaman nilai budaya pada setiap generasi mengakibatkan seluruh potensi tidak berkembang maksimal.…”
Section: Pendahuluanunclassified
“…Saladin S. Teo menyoroti pendidikan dan gaya hidup orang Bajo menyimpulkan bahwa secara umum perkembangan ilmu pengetahuan, kemajuan teknologi serta perubahan sosial tidak banyak mempengaruhi perubahan suku Bajo, termasuk aspek pendidikan dibandingkan dengan kelompok minoritas lainnya. Selain itu hasil penelitian menunjukkan bahwa suku bajo masih dianggap sebagai suku yang ketinggalan zaman, dipandang sebagai suku liar, susah diatrur, keras kepala, kasar, dan introvert (Basri et al, 2017). Kekuatan tradisi nenek moyang, penanaman nilai budaya pada setiap generasi mengakibatkan seluruh potensi tidak berkembang maksimal.…”
Section: Pendahuluanunclassified
“…Students always make contact with the community. Negative and incorrect cultural influences in the education field will also impact children's development and growth (Agustang & Gratitude, 2018;Basri et al, 2017;F. Gobel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From various literature studies that have been carried out, it is revealed that there is the strength of marine culture which can be used as a basis in liberating coastal communities from the shackles of underdevelopment, sociocultural poverty, and developing resources and strengthening the competitiveness of the nation [5]; [6]; [7]; [8]; [9]; [10]; [11]; [12]; [13]; [14]. This is in line with the sustainable development paradigm, which emphasizes the importance of the economic, environmental, and socio-cultural sustainability of local communities.…”
Section: Introductionmentioning
confidence: 99%